The climate in Poland (central Europe) in the first half of the last millennium, revisited - R. Przybylak; R. Przybylak; P. Oliński; P. Oliński; M. Koprowski; M. Koprowski; E. Szychowska-Krąpiec; M. Krąpiec; A. Pospieszyńska; A. Pospieszyńska; R. Puchałka; R. Puchałka (Climate of the Past, 2023)
The article presents updated knowledge on climate change in Poland (central Europe) in the first half of the last millennium (1001–1500). This knowledge is required to delimit the existence, duration, and scale of the Medieval Warm Period (MWP, also called the Medieval Climate Anomaly, MCA, here). To this end, it employs all available quantitative climate reconstructions created for Poland in the last 2 decades and four new reconstructions using three dendrochronological series and an extensive database of historical source data on weather conditions. The growth of conifers in lowland and upland Poland depends on the temperature in the cold season, especially in February and March. All available reconstructions based on dendrochronology data represent this time of the year. Summer temperatures were reconstructed using biological proxies and documentary evidence. The latter, however, is limited to the 15th century only. Winter temperature was used as the proxy for annual temperature proxies instead of the more usual use of summer temperature. The MWP occurred in Poland probably from the late 12th century to the first halves of the 14th or 15th centuries. All the analysed quantitative reconstructions suggest that the MWP in Poland was comparable to or warmer than the mean temperature in the period 1951–2000. The coldest conditions in the entire study period were noted in the first half of the 11th century (both winter and summer) and the second half of the 15th century (only winter). The greatest climate continentality occurred in the 15th century. Good agreement was found between the reconstructions of Poland's climate and many reconstructions available for Europe.